Plasmon based super resolution imaging for single molecular detection: Breaking the diffraction limit - Choi, Jong-ryul; Lee, Seunghun; Kim, Kyujung (Biomedical engineering letters, 2014)
Developments of super-resolution imaging techniques have considerable interests to detect and image tiny molecular events under a diffraction limit. Stimulated emission and depletion (STED) microscopy, photo-activated light microscopy (PALM) and structured illumination microscopy (SIM) are representative successful novel imaging techniques. Recently, surface plasmons (SP) based super resolution imaging techniques which can achieve super resolution with no deviation from conventional microscopic schematics have been actively investigated. In this paper, we explain the principle of SP phenomena which can apply for bioimaging, and introduce localized SP based super resolution imaging techniques to increase lateral and axial resolution below the diffraction limits. Three different novel techniques based on field localization are introduced to increase lateral resolution. Also, additional three imaging techniques based on extraordinary transmission and Förster resonance energy transfer are introduced to increase axial resolution. Consequently, we explore a future direction of SP based imaging researches for 3D spatiotemporal super resolution microscopy.